Modified nickel-cobalt-aluminum ternary positive electrode material, preparation method thereof and lithium battery
By using a composite cladding layer of transition metal nitride, aluminum-containing metal oxide and boric acid on the surface of lithium nickel cobalt aluminum ternary positive electrode material, the reduction of cycle stability and other performance problems caused by instability in the surface structure of the material is solved, and higher electrochemical performance and cycle life are achieved.
Patent Information
- Application Number
- CN202411929064.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
AI Technical Summary
The existing lithium nickel cobalt aluminum ternary cathode material has a degradation in the charging and discharging cycle due to the unstable surface structure of the lithium nickel cobalt aluminum ternary cathode material, resulting in a decrease in circulation stability, high residual alkali content, low capacity, and poor magnification and cycling performance.
By combining the surface of the bulk material with at least one of a transition metal nitride containing an effective metal and an aluminum-containing metal oxide and boric acid as the cladding material, a modified nickel-cobalt-aluminum ternary positive electrode material is formed.
The conductivity, Li+ diffusion rate and stability of the modified nickel-cobalt-aluminum ternary cathode material are improved, the residual alkali content and capacity loss are reduced, and the ratio and cycling performance are improved.
Smart Images

Figure CN119725468A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery materials, and in particular to a modified nickel-cobalt-aluminum ternary positive electrode material, a preparation method thereof, and a lithium battery. Background Art
[0002] Nickel-cobalt-aluminum ternary materials have become a popular choice for positive electrode materials for power lithium batteries due to their significant advantages in energy density, cost and safety. However, a key challenge of this high-nickel material lies in the particularity of its surface, which easily triggers unnecessary side reactions, and electrochemical reactions often occur preferentially on the surface of the material. Therefore, ensuring the stability of the surface structure of the material is particularly critical to improving the electrochemical performance of the entire electrode material. Unfortunately, the widely used lithium-nickel-cobalt-aluminum ternary positive electrode materials (NCA) often suffer from reduced cycle stability during charge and discharge cycles due to the instability of the surface structure.
[0003] In view of the above problems, it is particularly important to develop a method that can overcome the defects of the existing nickel-cobalt-aluminum ternary positive electrode materials, such as poor cycle stability, high residual alkali content, low capacity, and poor rate and cycle performance, so as to provide a modified nickel-cobalt-aluminum ternary positive electrode material, a preparation method thereof, and a lithium battery. Summary of the invention
[0004] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and provide a modified nickel-cobalt-aluminum ternary positive electrode material and a preparation method thereof and a lithium battery.
[0005] The present invention solves the technical problem by adopting the following technical solutions.
[0006] The present invention provides a modified nickel-cobalt-aluminum ternary positive electrode material, which comprises a bulk material and a coating layer coated on the surface of the bulk material, wherein the coating layer is composed of at least one of a transition metal nitride containing an effective metal and an aluminum-containing metal oxide and boric acid.
[0007] The present invention also provides a method for preparing the modified nickel-cobalt-aluminum ternary positive electrode material according to the above-mentioned method, comprising the following steps: mixing the bulk material with at least one of a transition metal nitride and an aluminum-containing metal oxide and boric acid and then sintering to obtain the modified nickel-cobalt-aluminum ternary positive electrode material.
[0008] The present invention also provides a lithium battery, wherein the positive electrode of the lithium battery comprises the modified nickel-cobalt-aluminum ternary positive electrode material or the modified nickel-cobalt-aluminum ternary positive electrode material prepared by the above-mentioned preparation method.
[0009] The present invention has the following beneficial effects: The present invention provides a modified nickel-cobalt-aluminum ternary positive electrode material, a preparation method thereof and a lithium battery. The present invention is modified by coating with at least one of binary nitrides containing effective metals or aluminum-containing metal oxides and boric acid. The surface coating not only enhances the interface dynamics, so that the modified nickel-cobalt-aluminum ternary positive electrode material has good ion diffusion capacity, but also avoids direct contact between the bulk material and the electrolyte, thereby reducing the side reaction between the bulk material and the electrolyte. The obtained modified nickel-cobalt-aluminum ternary positive electrode material has high conductivity and Li + The high diffusion rate, high stability, low residual alkali content, high discharge capacity, better rate and cycle performance make the lithium-ion battery prepared using the above-mentioned modified nickel-cobalt-aluminum ternary positive electrode material have better electrical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0011] Figure 1 This is the SEM image of the sample prepared in Example 1; Figure 2 XRD diffraction pattern of the sample prepared in Example 1; Figure 3 The first charge and discharge performance diagram of the button batteries of Example 1 and Comparative Example 1; Figure 4 The 45°C charge and discharge cycle performance diagram of the button batteries of Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0012] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0013] The following is a detailed description of a modified nickel-cobalt-aluminum ternary positive electrode material, a preparation method thereof, and a lithium battery provided in an embodiment of the present invention.
[0014] In the first aspect, an embodiment of the present invention provides a modified nickel-cobalt-aluminum ternary positive electrode material, which includes a bulk material and a coating layer coated on the surface of the bulk material, wherein the coating layer is composed of at least one of a transition metal nitride containing an effective metal and an aluminum-containing metal oxide and boric acid.
[0015] Studies have shown that as the nickel content of nickel-cobalt-aluminum ternary cathode materials increases, the cycle stability and safety of ultra-high nickel ternary cathode materials are worse than those of high nickel ternary cathode materials. The production conditions are relatively harsh, and the sealing, temperature and humidity, and CO2 control of production equipment are required to be higher. Ultra-high nickel content brings higher Li + / Ni 2+ Mixed arrangement, more lattice distortion, microcracks and lattice oxygen release, more violent surface side reactions, and higher residual lithium content on the surface will affect the safety and cycle performance of ultra-high nickel ternary materials. The present invention optimizes the coating sintering process of ternary materials, and uses at least one of binary compounds containing effective metals or aluminum-containing metal oxides and boric acid as coating sources for composite coating, so as to optimize the coating effect of nickel-cobalt-aluminum ternary positive electrode materials and prepare a nickel-cobalt-aluminum ternary positive electrode material with better physical and chemical properties. At the same time, it improves the problems of low material structure stability, high residual lithium, low capacity, and poor rate and cycle performance.
[0016] In some optional embodiments, the composition of the bulk material is LiNi x Co y M 1-x-y O2, wherein: 0.90≤x≤0.98, 0≤y<0.8, and M is at least two elements selected from Mn, Ti, Zr, Sr, Mo, Mg, Sb, V, Ta, Sn, Nb, B, Sc, Y, Mo, La and W.
[0017] The embodiment of the present invention provides a modified nickel-cobalt-aluminum ternary positive electrode material, in which a doping element M is doped into the inner layer of the matrix positive electrode material. 4+ With Y 4+ Modification and doping not only expand the sintering temperature range of the material, but also increase the Li + / Ni 2+ While mixing, a small amount of Ni 3+ Reduction to Ni 2+ or induce the formation of Li vacancies, greatly promoting the + Diffusion transport, part of Li + Migrate to the nickel layer to act as atomic columns to prevent the collapse of the layered plane during charge and discharge. Doping also reduces the anisotropic volume change caused by the H2-H3 phase transition of the material and inhibits the loss of lattice oxygen, ensuring the structural stability of the inner layer matrix of the invented positive electrode material.
[0018] In some optional embodiments, the aluminum-containing metal oxide includes at least one of cerium aluminate, lanthanum strontium aluminate, and magnesium aluminate, and the transition metal nitride includes at least one of molybdenum nitride, cobalt nitride, and tungsten nitride.
[0019] In some optional embodiments, the particle size of the modified nickel-cobalt-aluminum ternary positive electrode material is 3 μm to 15 μm, and the thickness of the coating layer is 3 nm to 10 nm.
[0020] In the second aspect, an embodiment of the present invention also provides a method for preparing the modified nickel-cobalt-aluminum ternary positive electrode material according to the above-mentioned method, comprising the following steps: mixing the bulk material with at least one of a transition metal nitride containing an effective metal and an aluminum-containing metal oxide and boric acid and then sintering to obtain a modified nickel-cobalt-aluminum ternary positive electrode material.
[0021] In some optional embodiments, the preparation of the bulk material comprises the following steps: Ni x Co y (OH)2 precursor A, lithium source B, aluminum source C and M source are mixed to obtain a mixed material D, and the mixed material D is sintered once to obtain a bulk material E; wherein: The mixer speed during the mixing process is 900rpm~1200rpm, the mixing temperature is 25℃~45℃, and the time is 40min~60min; the molar ratio of the lithium source to the precursor A in the mixed material D is Li / (Ni+Co)=1.04~1.07; the aluminum source C includes at least one of aluminum hydroxide, aluminum oxide, aluminum nitrate, aluminum isopropoxide, and aluminum sulfate, and the mass fraction of the Al element in the aluminum source C to the precursor A is 1000ppm~5000ppm; the M source includes at least one of the oxide, nitrate, and sulfate of the M element, and the mass fraction of the M element in the M source to the precursor A is 1000ppm~10000ppm, and the M element includes at least two elements of Mn, Ti, Zr, Sr, Mo, Mg, Sb, V, Ta, Sn, Nb, B, Sc, Y, Mo, La and W; the lithium source B includes at least one of lithium carbonate, lithium hydroxide, lithium acetate, and lithium oxalate.
[0022] In some optional embodiments, the conditions for the primary sintering include: placing the mixed material D into a box furnace, first heating it to 450°C~600°C at a rate of 2°C / min~10°C / min in an oxygen-containing atmosphere, heat treating it for 2h-4h, then heating it to 650°C~750°C, heat sintering it for 10h~15h, then cooling, crushing, sieving, washing, and vacuum drying to obtain the bulk material E.
[0023] In some optional embodiments, the preparation of the modified nickel-cobalt-aluminum ternary positive electrode material comprises: mixing the bulk material E with at least one of a transition metal nitride containing an effective metal and an aluminum-containing metal oxide and boric acid to obtain a mixed material F, and performing secondary sintering on the mixed material F to obtain a modified nickel-cobalt-aluminum ternary positive electrode material; wherein: The mixer speed during the mixing process is 800rpm~1000rpm, the mixing temperature is 20℃~45℃, and the mixing time is 20min~40min; boric acid accounts for 1000ppm of the total mass of the bulk material E, and the metal elements in the aluminum-containing metal oxide and / or transition metal nitride account for 200ppm~2000ppm of the total mass of the bulk material E; the aluminum-containing metal oxide includes at least one of cerium aluminate, lanthanum strontium aluminate, and magnesium aluminate, and the transition metal nitride includes at least one of molybdenum nitride, cobalt nitride, and tungsten nitride.
[0024] In some optional embodiments, the conditions for the secondary sintering include: placing the mixed material F into a box furnace, heating it to 250°C~400°C at a rate of 2°C / min~10°C / min in an oxygen-containing atmosphere, sintering it at this temperature for 5h~12h, then cooling, crushing, and sieving to obtain a modified nickel-cobalt-aluminum ternary positive electrode material, in which the Li element in the modified nickel-cobalt-aluminum ternary positive electrode material accounts for 6.6wt%~7.4wt% of the total mass of the modified nickel-cobalt-aluminum ternary positive electrode material.
[0025] The embodiment of the present invention provides a preparation method of the modified nickel-cobalt-aluminum ternary positive electrode material according to the above, and the surface of the bulk material is coated and modified by at least one of the binary nitride containing effective metals or aluminum-containing metal oxides and boric acid materials. On the one hand, each metal compound used in the present invention not only has good electrical conductivity, thermal conductivity and chemical stability of acid and alkali corrosion resistance, but also has the characteristics of high melting point and high mechanical strength. In addition, more importantly: if the bulk material is heat-treated at a specific temperature by cerium aluminate, part of the cerium aluminate, boric acid and residual lithium in the bulk material are heat-treated at high temperature, while consuming the residual lithium, a mixed fast ion conductor composite coating layer of lithium borate, lithium aluminate and lithium cerate is formed, which greatly reduces the residual lithium content on the surface of the bulk material, improves the interface transport kinetics of Li and inhibits parasitic side reactions, which is beneficial to improve the electrochemical properties of the bulk material. The acid and alkali corrosion resistance of cerium aluminate can also effectively inhibit the dissolution of the Ni element in the coated bulk material, and effectively avoids the direct contact reaction corrosion of the bulk material surface with the electrolyte, reduces the side reactions of the electrolyte, and improves the cycle stability of the bulk material. The high mechanical strength of cerium aluminate can also effectively inhibit the particle breakage in the coated bulk material, and effectively avoid the direct contact reaction corrosion between the internal particle surface and the electrolyte after the bulk material particles are broken, reducing the side reaction of the electrolyte, improving the cycle stability of the material and reducing capacity loss. On the other hand, Ce surface doping reduces the bond energy of Li-O bonds, and the Li vacancies formed can accelerate the Li + transmission rate; In addition, Ce 4+ It has strong oxidation ability and can remove Ni 2+ Oxidized to Ni 3+This reduces the formation of surface salt rock phase and further maintains the integrity and stability of the crystal structure; surface coating not only enhances the interface dynamics, making the composite material have good ion diffusion capacity, but also avoids direct contact between the bulk material and the electrolyte, reducing the side reaction between the bulk material and the electrolyte. Based on this structure, the bulk material has high conductivity and Li + High diffusion rate, high stability, low residual lithium, high discharge capacity, better rate and cycle performance.
[0026] The modified nickel-cobalt-aluminum ternary positive electrode material preparation method provided by the present invention is simple and has strong operability. The sintering conditions can be adjusted based on the existing mature production line process and are suitable for large-scale production. It provides a feasible strategy for preparing lithium-ion battery positive electrode materials with high energy density and superior safety performance.
[0027] In a third aspect, an embodiment of the present invention provides a lithium battery, wherein the positive electrode of the lithium battery includes the modified nickel-cobalt-aluminum ternary positive electrode material or the modified nickel-cobalt-aluminum ternary positive electrode material prepared by the above-mentioned preparation method.
[0028] As can be seen from the above, the present invention provides a modified nickel-cobalt-aluminum ternary positive electrode material and its preparation method and lithium battery, which adopts a combination of multi-element doping and surface modification to improve the defects of low material structure stability, severe particle breakage, high residual lithium, low capacity, poor rate and cycle performance. The internal composition of the modified nickel-cobalt-aluminum ternary positive electrode material is LiNi x Co y M 1-x-y O2, wherein: 0.90≤x≤0.98, 0≤y<0.8, M is at least two elements selected from Mn, Ti, Zr, Sr, Mo, Mg, Sb, V, Ta, Sn, Nb, B, Sc, Y, Mo, La and W. The outer layer is a binary nitride containing an effective metal or a metal oxide containing aluminum and boric acid as a composite coating layer.
[0029] The present invention will be further described below in conjunction with the embodiments.
[0030] Example 1 A method for preparing a modified nickel-cobalt-aluminum ternary positive electrode material comprises the following steps: 1. Weigh Ni according to the molar ratio of lithium source to precursor: Li / (Ni+Co)=1.07 0.96 Co 0.04 (OH)2 precursor A and battery-grade lithium hydroxide B, and aluminum hydroxide C accounting for 4000ppm of the precursor mass and a total of 3500ppm of nano-grade additives zirconium oxide (2500ppm) and yttrium oxide (1000ppm) are weighed and mixed evenly using a high-speed mixer, the speed of the high-speed mixer is 1000rpm, the mixing time is 45min, and the mixing temperature is 25-45°C to obtain a mixed material D; 2. The mixed material D obtained in step 1 is placed in a box furnace, and in an oxygen atmosphere, the temperature is first raised to 550°C at a rate of 3°C / min, and then the temperature is further raised to 725°C after heat treatment for 3 hours, and the mixture is sintered for 13 hours, followed by cooling, crushing, sieving, washing, and vacuum drying to obtain the bulk material E; 3. Next, weigh 1000ppm of nano-scale cerium aluminate and 1000ppm of boric acid, which account for the total mass of bulk material E, and add them to the bulk material E obtained in step 2. Mix them evenly using a high-speed mixer at a speed of 1000rpm, a mixing time of 30min, and a mixing temperature of 20-45°C to obtain a mixed material F. 4. Place the mixed material F obtained in step 3 into a box furnace, heat it to 325°C at a rate of 3°C / min in an oxygen atmosphere, sinter it for 9 hours, then cool it, crush it, and sieve it.
[0031] Figure 1 This is a surface morphology SEM image of the product prepared in Example 1. The surface of the product particles is relatively evenly coated, and there is no obvious agglomeration of additives on the particle surface, and only a small amount of additives is retained; Figure 2 The XRD diffraction pattern of the product prepared in Implementation 1 shows no other impurity peaks compared with the standard card, indicating that the coating layer does not affect the structure of the bulk material E itself.
[0032] Example 2 1. Operate according to steps 1 to 2 of Example 1; 2. Next, weigh 1000 ppm of nano-scale cobalt nitride and 1000 ppm of boric acid accounting for the total mass of bulk material E and mix them with bulk material E to obtain material F. The relevant parameters are kept consistent with step 3 in embodiment 2. The difference between this step and step 1 in embodiment 1 is that the type of metal compound in step 3 is different. 3. The subsequent operations are all carried out according to step 4 in Example 1.
[0033] Example 3 1. Operate according to steps 1 to 2 of Example 1; 2. Next, weigh 1000ppm of nano-scale lanthanum strontium aluminate and 1000ppm of boric acid accounting for the total mass of bulk material E and mix them with bulk material E to obtain material F. The relevant parameters are kept consistent with step 3 in embodiment 2. The difference between this step and step 1 in embodiment 1 is that the types of metal compounds in step 3 are different. 3. The subsequent operations are all carried out according to step 4 in Example 1.
[0034] Example 4 1. Operate according to steps 1 to 2 of Example 1; 2. Next, weigh 1000ppm of nano-scale tungsten nitride and 1000ppm of boric acid accounting for the total mass of bulk material E and mix them with bulk material E to obtain material F. The relevant parameters are kept consistent with step 3 in embodiment 2. The difference between this step and step 1 in embodiment 1 is that the type of metal compound in step 3 is different. 3. The subsequent operations are all carried out according to step 4 in Example 1.
[0035] Comparative Example 1 The steps 1 and 2 of Example 1 are followed, but the nano-scale additives zirconium oxide and yttrium oxide are not added; The remaining steps are prepared according to 3-4 in Example 1, but in step 3, no boric acid and metal compound are added.
[0036] Comparative Example 2 1. Operate according to steps 1 to 2 of Example 1; 2. The remaining steps are prepared according to 3-4 in Example 1, but in step 3, boric acid and the metal compound cerium aluminate are not added.
[0037] Comparative Example 3 1. Operate according to steps 1 to 2 of Example 1; 2. The remaining steps are carried out according to 3-4 of Example 1, except that in step 3, only boric acid is added without adding the metal compound cerium aluminate.
[0038] Comparative Example 4 1. Operate according to steps 1 to 2 of Example 1; 2. The remaining steps are carried out according to 3-4 of Example 1, except that in step 3, only cerium aluminate is added without boric acid.
[0039] Comparative Example 5 1. According to step 1 of Example 1, weigh Ni 0.96 Co 0.04 (OH)2 precursor A and battery-grade lithium hydroxide B, and weigh 5000ppm of aluminum hydroxide C and 5000ppm of nano-grade additives zirconium oxide (3000ppm) and yttrium oxide (2000ppm) respectively. The mixing process is consistent with step 1 in Example 1 to obtain a mixed material D; 2. The mixed material D obtained in step 1 is placed in a box furnace, and in an oxygen atmosphere, the temperature is first raised to 550°C at a rate of 3°C / min, and then the temperature is further raised to 750°C after heat treatment for 3 hours, and the mixture is sintered for 15 hours, followed by cooling, crushing, sieving, washing, and vacuum drying to obtain the bulk material E; 3. Next, weigh 2000 ppm of nano-sized cerium aluminate and 2000 ppm of boric acid, which account for the total mass of bulk material E, and add them to the bulk material E obtained in step 2. Mix them evenly using a high-speed mixer. The mixing process is consistent with step 3 in Example 1 to obtain a mixed material F. 4. Place the mixed material F obtained in step 3 into a box furnace, heat it to 400°C at a rate of 3°C / min in an oxygen atmosphere, sinter it for 12 hours, then cool it, crush it, and sieve it.
[0040] Comparative Example 6 1. Weigh the relevant materials according to Example 1 in step 1, and mix them evenly using a high-speed mixer at a speed of 1200 rpm, a mixing time of 45 min, and a mixing temperature of 50° C. to obtain a mixed material D; 2. Carry out the operation according to step 2 in Example 1 to obtain bulk material E; 3. According to step 2 in Example 1, weigh the modified additive, add it to the bulk material E obtained in step 2, and mix it evenly using a high-speed mixer at a speed of 1200 rpm, a mixing time of 30 min, and a mixing temperature of 50° C. to obtain a mixed material F; 4. Perform the operation according to step 4 in Example 1.
[0041] Electrochemical performance test: The products obtained in Examples 1 to 4 and Comparative Examples 1 to 6 were used as positive electrode materials to make button batteries for electrochemical performance testing. The production method is: a. The products obtained in the embodiment and the comparative example were stirred in a ratio of positive electrode material powder: conductive agent (SP): adhesive (PVDF) = 90:5:5 to form a uniformly dispersed positive electrode slurry, and the slurry was coated, punched, and vacuum dried; a metal lithium sheet was used as the negative electrode material of the counter electrode, and a polypropylene film with micropores was used as a battery separator; the solvent volume ratio was 1:1 ethylene carbonate (EC) / dimethyl carbonate (DMC), 1 mol / L LiPF6 was used as the electrolyte, and a 2032-type button battery was assembled in a glove box filled with dry high-purity argon and allowed to stand for 8 hours; b. The button cells that have been left to stand were charged and discharged at an ambient temperature of 25°C, 3.0-4.3V, and a current rate of 0.2C to test the electrochemical performance of Examples 1-4 and Comparative Example 1. The first discharge efficiency was calculated, i.e., first efficiency = first discharge specific capacity / first charge specific capacity*100%.
[0042] c. At 45°C, at 3.0-4.3V with 1C charge / 1C discharge, the cycle performance of Examples 1-4 and Comparative Examples 1-6 was tested, and the capacity retention rate after 50 cycles was calculated. The formula is as follows: capacity retention rate = 50th discharge specific capacity / first discharge specific capacity * 100%.
[0043] Please refer to Table 1 for specific test data.
[0044] Table 1 Electrical performance test results
[0045] Combining the above table 1 and Figure 3-Figure 4 It can be seen that compared with Comparative Example 1, the electrical properties (first effect and discharge specific capacity) and high-temperature cycle stability of the positive electrode materials prepared in each embodiment of the present invention have been significantly improved. The method of this embodiment effectively improves the first effect of the material and improves the charge and discharge performance of the material; at the same time, it also shows good cycle performance at a high temperature of 45°C and a rate of 1C, which further illustrates that its rate performance has also been improved. It is explained that the composite coating of cerium aluminate and boric acid effectively avoids the direct contact reaction between the surface of the positive electrode material and the electrolyte, prevents the occurrence of electrolyte decomposition side reactions, improves the cycle stability of the positive electrode material, and greatly improves the cycle life of the lithium battery. It is speculated that the possible reasons are: the strong acid and alkali corrosion resistance of the transition metal nitride containing effective metals and / or aluminum-containing metal oxides in the modified nickel-cobalt-aluminum ternary positive electrode material enables the coated positive electrode material to effectively reduce the dissolution of nickel elements; in addition, because boric acid reacts with the residual lithium of the positive electrode material to form a lithium borate coating layer of a fast ion conductor, the modified nickel-cobalt-aluminum ternary positive electrode material has very excellent electrochemical properties.
[0046] Comparative Examples 1 to 6 show that the electrical properties (first efficiency and discharge specific capacity) and high temperature cycle stability of the products prepared in the embodiments of the present invention are significantly reduced. In Comparative Examples 1 to 4, no coating is performed or a single coating agent is used for coating. The relevant performance of the lithium batteries prepared using the products in Comparative Examples 1 to 4 is relatively poor. The higher dopant and coating agent in Comparative Example 5 is expected to require a higher sintering temperature, which greatly deteriorates the physical and chemical properties of the material. The high content of dopant and coating agent reduces the content of active lithium and hinders the Li + Transmission. The higher sintering temperature destroys the crystal structure of the material and increases the cation mixing, which further leads to the reduction of the physical and chemical properties of the material. The higher coating speed and coating temperature in Comparative Example 6 greatly reduce the coating uniformity of the dopant and coating agent, thus failing to achieve the ideal coating effect. The high speed will cause the material particles to break and cause the electrochemical properties of the material to decrease. In addition, the coating temperature is too high, which will cause the local additives and coating agents to deteriorate, and ultimately lead to the reduction of material performance.
[0047] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A modified nickel-cobalt-aluminum ternary positive electrode material, characterized in that: The modified nickel-cobalt-aluminum ternary positive electrode material comprises a bulk material and a coating layer coated on the surface of the bulk material, wherein the coating layer is composed of at least one of a transition metal nitride containing an effective metal and an aluminum-containing metal oxide and boric acid.
2. The modified nickel-cobalt-aluminum ternary positive electrode material according to claim 1, characterized in that: The composition of the bulk material is LiNi x Co y M 1-x-y O2, wherein: 0.90≤x≤0.98, 0≤y<0.8, and M is at least two elements selected from Mn, Ti, Zr, Sr, Mo, Mg, Sb, V, Ta, Sn, Nb, B, Sc, Y, Mo, La and W.
3. The modified nickel-cobalt-aluminum ternary positive electrode material according to claim 1, characterized in that: The aluminum-containing metal oxide includes at least one of cerium aluminate, lanthanum strontium aluminate, and magnesium aluminate, and the transition metal nitride includes at least one of molybdenum nitride, cobalt nitride, and tungsten nitride.
4. The modified nickel-cobalt-aluminum ternary positive electrode material according to any one of claims 1 to 3, characterized in that: The particle size of the modified nickel-cobalt-aluminum ternary positive electrode material is 3 μm to 15 μm, and the thickness of the coating layer is 3 nm to 10 nm.
5. A method for preparing a modified nickel-cobalt-aluminum ternary positive electrode material according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: mixing a bulk material with at least one of a transition metal nitride containing an effective metal and an aluminum-containing metal oxide and boric acid, and then sintering the mixture to obtain a modified nickel-cobalt-aluminum ternary positive electrode material.
6. The preparation method according to claim 5, characterized in that: The preparation of the bulk material comprises the following steps: According to the proportion of Ni x Co y (OH)2 precursor A, lithium source B, aluminum source C and M source are mixed to obtain a mixed material D, and the mixed material D is sintered once to obtain a bulk material E; wherein: The mixer speed during the mixing process is 900rpm~1200rpm, the mixing temperature is 25℃~45℃, and the time is 40min~60min; the molar ratio of the lithium source in the mixed material D to the precursor A is Li / (Ni+Co)=1.04~1.07; the aluminum source C includes at least one of aluminum hydroxide, aluminum oxide, aluminum nitrate, aluminum isopropoxide, and aluminum sulfate, and the mass fraction of the Al element in the aluminum source C to the precursor A is 1000ppm~5000ppm; the M source includes at least one of the oxide, nitrate, and sulfate of the M element, and the mass fraction of the M element in the M source to the precursor A is 1000ppm~10000ppm, and the M element includes at least two elements of Mn, Ti, Zr, Sr, Mo, Mg, Sb, V, Ta, Sn, Nb, B, Sc, Y, Mo, La and W; the lithium source B includes at least one of lithium carbonate, lithium hydroxide, lithium acetate, and lithium oxalate.
7. The preparation method according to claim 6, characterized in that: The conditions of the primary sintering include: placing the mixed material D into a box furnace, heating it to 450°C~600°C at a rate of 2°C / min~10°C / min in an oxygen-containing atmosphere, heat-treating it for 2h-4h, then heating it to 650°C~750°C, heat-treating it for 10h~15h, cooling, crushing, sieving, washing, and vacuum drying to obtain a bulk material E.
8. The preparation method according to claim 7, characterized in that: The preparation of the modified nickel-cobalt-aluminum ternary positive electrode material comprises: mixing a bulk material E with at least one of a transition metal nitride containing an effective metal and an aluminum-containing metal oxide and boric acid to obtain a mixed material F, and performing secondary sintering on the mixed material F to obtain a modified nickel-cobalt-aluminum ternary positive electrode material; wherein: The mixer speed during the mixing process is 800rpm~1000rpm, the mixing temperature is 20℃~45℃, and the time is 20min~40min; the boric acid accounts for 1000ppm of the total mass of the bulk material E, and the metal elements in the aluminum-containing metal oxide and / or the transition metal nitride account for 200ppm~2000ppm of the total mass of the bulk material E; the aluminum-containing metal oxide includes at least one of cerium aluminate, lanthanum strontium aluminate, and magnesium aluminate, and the transition metal nitride includes at least one of molybdenum nitride, cobalt nitride, and tungsten nitride.
9. The preparation method according to claim 8, characterized in that: The conditions of the secondary sintering include: placing the mixed material F into a box furnace, heating it to 250°C~400°C at a rate of 2°C / min~10°C / min in an oxygen-containing atmosphere, sintering it at this temperature for 5h~12h, then cooling, crushing, and sieving to obtain a modified nickel-cobalt-aluminum ternary positive electrode material, wherein the Li element in the modified nickel-cobalt-aluminum ternary positive electrode material accounts for 6.6wt%~7.4wt% of the total mass of the modified nickel-cobalt-aluminum ternary positive electrode material.
10. A lithium battery, characterized in that: The lithium battery positive electrode comprises the modified nickel-cobalt-aluminum ternary positive electrode material described in any one of 1 to 4 or the modified nickel-cobalt-aluminum ternary positive electrode material prepared by the preparation method described in any one of 5 to 9.
Citation Information
Patent Citations
Composite cathode material, preparation method and lithium ion battery
CN108832093A
Ternary positive electrode material as well as preparation method and application thereof
CN115275195A
Lanthanum aluminate coated nickel cobalt lithium manganate ternary positive electrode material and preparation method thereof
CN115632115A
Positive electrode material and preparation method and application thereof
CN116581256A
Ultrahigh-nickel single-crystal positive electrode material as well as preparation method and application thereof
CN116845192A
Cited By
Composite coated modified nickel-cobalt-manganese ternary positive electrode material as well as preparation method and application thereof
CN120895632A
A composite-coated modified nickel-cobalt-manganese ternary cathode material, its preparation method and application
CN120895632B
Modified nickel-cobalt-aluminum ternary positive electrode material and preparation method therefor, and lithium battery
WO2026137786A1